Subprime facts: What (we think) we know about the subprime crisis and what we don't - Christopher L. Foote; Kristopher Gerardi; Lorenz Goette; Paul S. Willen (Federal Reserve Bank of Boston, 2008)
Using a variety of datasets, we document some basic facts about the current subprime crisis. Many of these facts are applicable to the crisis at a national level, while some illustrate problems relevant only to Massachusetts and New England. We conclude by discussing some outstanding questions about which the data, we believe, are not yet conclusive.
Keywords: D11; D12; G21; R20; 330; Finanzmarktkrise; Subprime-Hypothek; USA